Pendidikan Pranikah bagi Calon Pengantin dalam Upaya Mewujudkan Keluarga Sakinah - Warits, Hakimah; Anshori, Ari; Hidayat, Syamsul (Griya Widya: Journal of Sexual and Reproductive Health, 2025)
Background: Premarital education is a form of education for couples who will marry with the aim of preparing couples to enter married life. The content of pre-marital education is in the form of information, knowledge and basic skills training related to aspects that are expected to strengthen the relationship of the couple in order to be able to maintain married life. And the purpose of this study is to find out how education before entering the marriage stage is through a premarital marriage guidance program for brides and grooms at the Office of the Ministry of Religion, Sukoharjo.  Method: This research method itself is through a description with a qualitative approach. For data analysis using logical thinking, where a syllogism is built based on specific things and leads to general conclusions.  Result: The premarital marriage guidance program for prospective brides is divided into two formats, namely: face-to-face guidance and independent guidance. The success of premarital marriage guidance for prospective brides cannot be separated from supporting factors, namely: Regency Ministry of Religion as the organizing agency, budget legitimized sources of funds, prospective brides who become participants, quality resource persons, appropriate materials, and adequate facilities. The obstacles, both limited funds, places, facilities and learning media. Implication: The Binwin facilitator in providing pre-marital guidance in an effort to create a sakinah family for the bride and groom. Novelty: The premarital marriage guidance program for prospective brides is divided into two formats, namely: face-to-face guidance and independent guidance